STRATEGI PENDEKATAN PARTICIPATORY RURAL APPRAISAL (PRA) DALAM MEWUJUDKAN KEMANDIRIAN MASYARAKAT TRANSMIGRASI DI KAMPUNG MARGA MULIA DISTRIK SEMANGGA - Hubertus Oja; Hesty Tambajong (SOCIETAS, 2015)
Development policy for the currentis put emphasis on the concrete efforts so as to motivate the public to actively participate in the implementation of development towards independence of the civil society. This research have a purpose to know a strategic approach to participatory rural appraisal (PRA) to realize the independence of the transmigration community in Marga Mulia Village.This research was held in the Marga Mulia Village, Semangga District. The researh used a qualitative method. Data collection techniques consists of literature review and field studies through a process of observation, interviews and documentation. Data analysis included data reductation, data presentation and conclussion.The results showed that the participatory rural appraisal (PRA) approach in Marga Mulia Village, Semangga District don’t yet optimal. The people is not yet fully involved in the development process of the village.The emphasis on participatory rural appraisal (PRA) approach requires active community involvement in the development stages of planning, implementatages of planning, implementation, monotoring and evaluation. The involvement of the society wasion, monotoring and evaluation. The involvement of the society was involved in the planning and implementation stages of involved in the planning and implementation stages of development. At the stages of monitoring and evaluation has been no direct socirect society involvement as the embodiment of social control to create a development climate for participatory ety involvement as the embodiment of social control to create a development climate for participatory development and democracy